Romantic Narrative Shelley, Hays, Godwin, Wollstonecraft - Rajan, Tilottama (Johns Hopkins University Press, 2010)
Often identified with its lyric poetry, Romanticism has come to be dismissed by historicists as an ineffectual idealism. By focusing on Romantic narrative, noted humanist Tilottama Rajan takes issue with this identification, as well as with the equation of narrative itself with the governmental apparatus of the Novel. Exploring the role of narrativity in the works of Romantic writers, Rajan also reflects on larger disciplinary issues such as the role of poetry versus prose in an emergent modernity and the place of Romanticism itself in a Victorianized nineteenth century.While engaging both genres, Romantic Narrative responds to the current critical shift from poetry to prose by concentrating, paradoxically, on a poetics of narrative in Romantic prose fiction. Rajan argues that poiesis, as a mode of thinking, is Romanticism's legacy to an age of prose. She elucidates this thesis through careful readings of Shelley's Alastor and his Gothic novels, Godwin's Caleb Williams and St. Leon, Hays' Memoirs of Emma Courtney, and Wollstonecraft's The Wrongs of Woman. Rajan, winner of the Keats-Shelley Association's Distinguished Lifetime Award and a fellow of the Royal Society of Canada, is one of Romanticism's leading scholars. Effective, articulate, and readable, Romantic Narrative will appeal to scholars in both nineteenth-century studies and narrative theory.